Responses of macroalgae to CO2 enrichment cannot be inferred solely from their inorganic carbon uptake strategy. Issue 1 (14th December 2018) - van der Loos, Luna M.; Schmid, Matthias; Leal, Pablo P.; McGraw, Christina M.; Britton, Damon; Revill, Andrew T.; Virtue, Patti; Nichols, Peter D.; Hurd, Catriona L.
Abstract: Increased plant biomass is observed in terrestrial systems due to rising levels of atmospheric CO2, but responses of marine macroalgae to CO2 enrichment are unclear. The 200% increase in CO2 by 2100 is predicted to enhance the productivity of fleshy macroalgae that acquire inorganic carbon solely as CO2 (non‐carbon dioxide‐concentrating mechanism [CCM] species—i.e., species without a carbon dioxide‐concentrating mechanism), whereas those that additionally uptake bicarbonate (CCM species) are predicted to respond neutrally or positively depending on their affinity for bicarbonate. Previous studies, however, show that fleshy macroalgae exhibit a broad variety of responses to CO2 enrichment and the underlying mechanisms are largely unknown. This physiological study compared the responses of a CCM species ( Lomentaria australis ) with a non‐CCM species ( Craspedocarpus ramentaceus ) to CO2 enrichment with regards to growth, net photosynthesis, and biochemistry. Contrary to expectations, there was no enrichment effect for the non‐CCM species, whereas the CCM species had a twofold greater growth rate, likely driven by a downregulation of the energetically costly CCM(s). This saved energy was invested into new growth rather than storage lipids and fatty acids. In addition, we conducted a comprehensive literature synthesis to examine the extent to which the growth and photosynthetic responses of fleshy macroalgae to elevated CO2 are related to their carbon acquisition strategies. Findings highlight that the responses of macroalgae to CO2 enrichment cannot be inferred solely from their carbon uptake strategy, and targeted physiological experiments on a wider range of species are needed to better predict responses of macroalgae to future oceanic change. Abstract : In this detailed physiological study, we tested the hypothesis that the responses of macroalgae to CO2 enrichment can be predicted by their carbon uptake strategy, by comparing growth, productivity, and biochemical responses of a macroalgal species with a carbon dioxide‐concentrating mechanism (CCM) with a species lacking this mechanism (non‐CCM). Growth and photosynthetic rates in the non‐CCM species were unaffected by CO2 enrichment, whereas for the CCM species, growth rates increased—opposite to current dogma. These experimental results, together with a new analysis of literature, reveal that carbon uptake strategy is a poor indicator of the responses of macroalgae to CO2 enrichment.